2020
DOI: 10.1021/acs.chemmater.0c04219
|View full text |Cite
|
Sign up to set email alerts
|

End-Functionalization of Diarylethene for Opto-Electronic Switching with High Fatigue Resistance

Abstract: A molecular and synthetic approach to strengthen the switching performance of diarylethene (DAE)-based organic transistors is proposed. By tuning the length of alkyl side chains of the biphenyl unit attached to 1,2-bis(5-biphenyl-2-methylthien-3-yl)perfluorocyclopentene (DAE), we show that the molecular environment for reversible photoisomerization of DAEs can be optimized. Four different DAEs are synthesized with different alkyl chains (DAE_C0, DAE_C1, DAE_C6, and DAE_C10), and ITIC is chosen to construct a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 63 publications
0
15
0
Order By: Relevance
“…Moreover, the UV–visible absorption spectra of pristine DPPDTT showed no change upon UV light irradiation, as shown in Figure S10, owing to the absence of an absorption band below 500 nm. Because of the satisfactory crystallographic compatibility, high photocyclization QY (0.76), high photocycloreversion QY (0.015), and enhanced chemical FR of DAE-316, the DPPDTT/DAE-316 FET device showed the highest photoprogrammable switching ratio of approximately 4405, which is the highest value among all the reports to date. , , …”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Moreover, the UV–visible absorption spectra of pristine DPPDTT showed no change upon UV light irradiation, as shown in Figure S10, owing to the absence of an absorption band below 500 nm. Because of the satisfactory crystallographic compatibility, high photocyclization QY (0.76), high photocycloreversion QY (0.015), and enhanced chemical FR of DAE-316, the DPPDTT/DAE-316 FET device showed the highest photoprogrammable switching ratio of approximately 4405, which is the highest value among all the reports to date. , , …”
Section: Resultsmentioning
confidence: 95%
“…The introduction of a reliable and reproducible mechanism that can selectively modulate the I DS level will allow the OFET to exhibit multiple I DS regimes beyond those of the typical two-regime I DS . One promising method to achieve such multiple I DS regimes in OFETs is by embedding photoprogrammable switching molecules within organic semiconductors (OSCs). The differences in the geometry and electronic structure of two different isomers of photoprogrammable switching molecules can be utilized to control the reversibility of various electronic properties. Azobenzene, diarylethene (DAE), spiropyran, and fulgide are well-known photoprogrammable switching molecules that have been used in various optoelectronic and colorimetric devices. Among them, DAE, which has a heterocyclic aryl group, is a very promising candidate for photoprogrammable switching devices owing to its relatively high chemical fatigue resistance (FR), thermal stability, and bistable energy levels.…”
Section: Introductionmentioning
confidence: 99%
“…[ 25 ] Synthesis of DAE–Bph–6F was reported in our previous study. [ 28 ] The synthesis details are described in Supporting Information.…”
Section: Methodsmentioning
confidence: 99%
“…Typically, diarylethene derivatives can function as wavelength-selective molecular switches with UV light (300-400 nm), inducing photocyclization (ring-closing) and visible light (400-700 nm), inducing photocycloreversion (ring-opening). [20][21][22][23][24][25][26][27][28][29] The light-intensity-dependent switching properties of DAB are utilized such that a gradually increasing intensity of ambient light (including both UV and visible wavelengths) gradually converts open isomers into closed isomers owing to the considerably higher quantum yield of photocyclization compared to that of the photocycloreversion of DAB, which is typical for diarylethenes. As shown in Figure 1b, under weak ambient illumination, DAB molecules contain mostly open isomers with a wide highest occupied molecular orbital (HOMO)-lowest unoccupied molecular orbital (LUMO) gap, and hence, do not affect the junction properties of Schottky OPDs.…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19][20] For example, it has been reported that diarylethene and its derivates can undergo efficient and reversible photochromism when irradiated with UV and visible light, ultimately allowing control of the luminescence of such compounds. [21][22][23][24][25] The combination of NIR phosphorescence and photochromism in a single diarylethene molecule could therefore render such a system widely applicable in various fields. However, to the best of our knowledge, photo-controlled pure organic NIR phosphorescence has yet to be reported in solution.…”
Section: Doi: 101002/smll202201821mentioning
confidence: 99%